Determinants of tax revenue in Indonesia with economic growth as a mediation variable - Dora Dessandy Maryantika; Suparna Wijaya (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
Tax revenue has an important role as the main source of state revenue. However, for several years, the realization of tax revenues has not been able to reach the target and the level of the tax ratio is still not ideal. This shows that tax revenue needs to be increased so that the factors that can affect tax revenue need to be analyzed. This study aims to examine the effect of corruption, government spending, and human development on tax revenues and the effect of economic growth in mediating these effects. The analysis was conducted on 10 provinces during 2010 to 2019 was selected using a purposive sampling technique and 100 observations were obtained. Multiple linear regression was used as a method to analyze the hypothesis. The results showed that (1) government spending, human development and economic growth had a positive effect on tax revenue, while corruption had no effect on tax revenue; (2) government spending and human development have a positive effect on economic growth, while corruption has no effect on economic growth; (3) economic growth mediates the effect of government spending and human development on tax revenues; (4) economic growth does not mediate the effect of corruption on tax revenues.